Effects of Different Cooking Methods on Nutritional Properties and Non-volatile Flavor Substances of Lyophyllum decastes - Xiaolong LI; Yan YANG; Wen LI; Yanfang LIU; Di WU; Huanling YANG; Wanchao CHEN; Jingjun LI (Shipin gongye ke-ji)
In order to explore the nutritional characteristics and non-volatile flavor substances under different cooking techniques, this study utilized fresh Lyophyllum decastes and subjected them to four different cooking methods: Steaming, boiling, air frying without oil and baking. The contents of polysaccharide, total phenol, protein and total dietary nutrients, as well as non-volatile flavor substances such as soluble sugar, free amino acid and 5'-nucleotide and equivalent umami concentration (EUC) in L. decastes treated by different cooking methods were analyzed by ion chromatography, high performance liquid chromatography and electronic tongue technology. The results showed that boiling significantly reduced the levels of polysaccharides, total phenols, protein, total dietary fiber, soluble sugar, free amino acid, and 5'-nucleotide flavor content. Conversely, baking was found to be the most effective method in preserving or even enhancing these nutritional and flavor profiles. The processing effects of steaming and air frying without oil fall between boiling and oven baking, with steaming retained more nutrients in L. decastes and produced a flavor profile similar to that of oven-baked samples. Principal component analysis (PCA) of electronic tongue data revealed significant variations in the flavor profiles of L. decastes across different cooking methods. The sample points for steaming and baking were closer together, indicating a smaller difference in taste after these two cooking methods. In contrast, the sample points for control, boiling, and air frying without oil were distributed in three different quadrants, with relatively large distances from each other, suggesting that these three cooking methods lead to greater differences in the flavor of L. decaste. This study examines the changes in nutritional components and non-volatile flavor compounds in L. decaste subjected to steaming, boiling, air frying without oil, and baking. Among these methods, baking preserves both nutrients and non-volatile flavor compounds most effectively, offering a theoretical basis for optimizing the cooking of L. decaste and other edible fungi.